PENGARUH FINANCING TO DEPOSIT RATIO (FDR), NON PERFORMING FINANCING (NPF), DAN BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) TERHADAP TINGKAT PROFITABILITAS (Studi Empiris pada Bank Umum Syariah yang terdaftar di Bursa Efek Indonesia pada tahun 2014-2017) - Isnaini Arofatul Azizah; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research aims to know the influence of the Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Operating Expenses per Operating Income (BOPO) against Profitability (ROA). The analysis technique used to test the hypothesis is multiple regression. The statistical test used consists of the f test to test the variables together, the test of determination, and the t test to test partially. The classic assumption test consists of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The research of this study indicate that the Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) variables has a significant negative effect on Profitability, while the Operating Expenses per Operating Income (BOPO) has no effect significant on Profitability. Keywords : Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) Operating Expenses per Operating Income (BOPO) and Profitability.